2015
DOI: 10.1016/j.abb.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The invertebrate Caenorhabditis elegans biosynthesizes ascorbate

Abstract: L-ascorbate, commonly known as vitamin C, serves as an antioxidant and cofactor essential for many biological processes. Distinct ascorbate biosynthetic pathways have been established for animals and plants, but little is known about the presence or synthesis of this molecule in invertebrate species. We have investigated ascorbate metabolism in the nematode Caenorhabditis elegans, where this molecule would be expected to play roles in oxidative stress resistance and as cofactor in collagen and neurotransmitter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 101 publications
(108 reference statements)
3
34
0
Order By: Relevance
“…In C. elegans ascorbate levels were highest in eggs, levels declined throughout larval growth, and were lowest in mixed age adults. In addition ascorbate levels were higher when worms were grown in liquid media compared to when they were cultured on agar plates, but ascorbate levels did not increase when worms were exposed to the free radical generator paraquat (Patananan et al 2015). We predict that the decreased level of galactonic acid-1,4-lactone with age is partially due to its conversion into ascorbate, as we measured ascorbate and DHA levels to increase during aging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In C. elegans ascorbate levels were highest in eggs, levels declined throughout larval growth, and were lowest in mixed age adults. In addition ascorbate levels were higher when worms were grown in liquid media compared to when they were cultured on agar plates, but ascorbate levels did not increase when worms were exposed to the free radical generator paraquat (Patananan et al 2015). We predict that the decreased level of galactonic acid-1,4-lactone with age is partially due to its conversion into ascorbate, as we measured ascorbate and DHA levels to increase during aging.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is unknown if C. elegans can convert galactonic acid-1,4-lactone into ascorbate as bioinformatic analysis did not detect an L-galactonic acid-1,4-lactone dehydrogenase in the C. elegans genome (Patananan et al 2015), but invertebrates may have evolved a unique, as of yet unidentified enzyme to catalyze this reaction. In support of this hypothesis C. elegans has been shown to synthesize both ascorbate and an unidentified hydrogenated lactone precursor to ascorbate, but the ascorbate synthesis pathway appears to be different from the pathways present in animals, plants, or protists, while ascorbate is not synthesized by E. coli (Patananan et al 2015). In C. elegans ascorbate levels were highest in eggs, levels declined throughout larval growth, and were lowest in mixed age adults.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Alexander et al [36] reported that C. elegans can synthesize L -ascorbic acid de novo . L -ascorbic acid serves as a potent antioxidant and participates in collagen biosynthesis in most mammals [37], but the function of L -ascorbic acid in C. elegans is not understood.…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbate biosynthesis pathways differ between animals, green plants and photosynthetic protists [2] , [62] while, as noted in the previous section, fungi synthesise a 5C analogue of ascorbate, D-erythroascorbate. Recent evidence suggests that the nematode Caenorhabditis elegans contains ascorbate but does not use any of the known pathways [63] . Ascorbate biosynthesis pathways have been well-reviewed [2] , [57] , [64] , [65] , [66] and recent developments are minimal, so they will only be outlined here ( Fig.…”
Section: Ascorbate Biosynthesismentioning
confidence: 99%